2016
DOI: 10.9767/bcrec.11.2.549.182-190
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study: Esterification of Free Fatty Acids (FFA) in Artificially Modified Feedstock Using Ionic Liquids as Catalysts

Abstract: The exploration of non-edible oils as a feedstock has been positively affect the economic viability of biodiesel production. Due to the high level of free fatty acid (FFA) in non-edible oils, esterification is needed to remove the acidity to the minimum level before base-catalyzed transesterification. In this study, 1-hexyl-3-methylimidazolium hydrogen sulphate (HMIMHSO4) was self-synthesized and compared with the commercialized ionic liquid, 1-butyl-3-methylimidazolium hydrogen sulphate (BMIMHSO4). HMIMHSO4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Ionic liquids (ILs) as organocatalysts are one of the most rapidly growing topics of chemistry research on new materials investigation in the last decade. Conventionally, ILs are entirely composed of cations and anions with the melting points lower than 100 • C [38][39][40]. However, ionic liquids are better described as liquid compounds that display ionic-covalent crystalline structures [41].…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) as organocatalysts are one of the most rapidly growing topics of chemistry research on new materials investigation in the last decade. Conventionally, ILs are entirely composed of cations and anions with the melting points lower than 100 • C [38][39][40]. However, ionic liquids are better described as liquid compounds that display ionic-covalent crystalline structures [41].…”
Section: Introductionmentioning
confidence: 99%
“…salts) which melt at or below 100 °C. These salts have attracted rising interest in the last decade, due to their unique properties, such as: high thermal and chemical stability, non-flammability, non-volatility, wide liquid-state temperature range, large electrochemical window, favorable salvation behavior, and ability to use as solvent, reagent and catalyst in organic synthesis [1][2][3][4][5][6][7][8][9][10]. Among the different kinds of ionic liquids, Brønsted acidic ones have been designed to replace solid acids and traditional mineral liquid acids to catalyze chemical transformations [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary study on esterification of free fatty acids (FFA) in artificially modified feedstock using ionic liquids as catalysts was studied by Roslan et al [9]. They found that BMIMHSO4 shows considerable potential to reduce the FFA in the feedstock as it is exhibit excellent catalytic activity due to lower alkyl chain of BMIMHSO4 compared to HMIMHSO4.…”
mentioning
confidence: 99%